A Clinical Study on the Effect of Anu Taila Nasya and Shatyadi Vati in Vataja Pratishyaya with special reference to Allergic Rhinitis (AYUSHDHARA, 2024)
Vataja Pratishyaya (Allergic Rhinitis) is well known for its recurrence and chronicity. Currently approximately 10-30% of adults and 40% of children are affected (feb 2023). A study 2022 revealed that COVID -19 could cause disturbances to the immune system, leading to unusual mast cell activation that may cause allergic flare-ups. Long term usage of nasal decongestants, causes Rhinitis Medicamentosa (RM). Keeping in view the limitations associated with long term usage of modern medications, there is a need to approach Ayurveda treatment for allergic rhinitis. So in present study Anu Taila Nasya and Shatyadi Vati were selected. The trial was conducted on 40 clinically diagnosed patients of Vataja Pratishyaya (allergic rhinitis). Study was carried out in a single group. Anu Taila in the form of Nasya therapy 8 drop of Marsha Nasya of 3 sitting and 2 drop of Pratimarsha Nasya in between 3 sitting of Marsha Nasya in both nostrils, once a day for 35 days along with Shatyadi Vati (500mg) 1 tab BD with lukewarm water for 35 days was given. Result was observed and data was statistically analysed before and after treatment. Highly significant results were found in subjective parameters as well as in objective parameters like sneezing (paroxysmal), nasal obstruction, running nose, itching in the nose, temporal headache, nasal congestion except IgE values (significant result).